The significance of DNA methylation profile in metastasis-related genes for the progression of colorectal cancer - Tokarz, P.; Pawlowska, E.; Bialkowska-Warzecha, J.; Blasiak, J. (Cellular and Molecular Biology, 2017)
DNA methylation, an epigenetic modification plays a role in the pathogenesis of colorectal cancer (CRC). CRC cases, both sporadic and familial, are often characterized by abnormal pattern of the cytosine methylation in CpG dinucleotides in regulatory regions of genes important for cancer transformation. Also genes mutated in CRC can have their epigenetic pattern altered and we suggest that changes in DNA methylation array can be important for CRC metastatic potential "’ the main reason of CRC-associated mortality. These genes are: KRAS, genes of the Rho family of GTPases, MACC1, Met, MTA1 and RASSF1A. In addition, genes encoding miRNA important for epithelial mesenchymal transition and other metastasis-related effects, such as mir-9, miR-34 and miR-210 can be good candidates for associating their DNA methylation profiles with CRC metastasis. Analysis of DNA methylation profile in various stages of CRC along with other genetic/epigenetic changes specific for all main stages of CRC transformation could help in anti-metastatic therapy immediately after CRC diagnosis. However, targeting DNA methylation pattern in CRC therapy is a conception, which requires further work to precisely change DNA methylation array, without affecting genes, whose expression should not be changed.